Air Pollution, Genetic Factors, and the Risk of Lung Cancer: A Prospective Study in the UK Biobank - Huang, Yanqian; Zhu, Meng; Ji, Mengmeng; Fan, Jingyi; Xie, Junxing; Wei, Xiaoxia; Jiang, Xiangxiang; Xu, Jing; Chen, Liang; Yin, Rong; Wang, Yuzhuo; Dai, Juncheng; et al. (American journal of respiratory and critical care medicine, 2021)
Both genetic and environmental factors contribute to lung cancer, but the degree to which air pollution modifies the impact of genetic susceptibility on lung cancer remains unknown. To investigate whether air pollution and genetic factors jointly contribute to incident lung cancer. We analyzed data from 455,974 participants (53% women) without previous cancer at baseline in the UK Biobank. The concentrations of particulate matter (PM) (PM ⩽2.5 μm in aerodynamic diameter [PM ], coarse PM between 2.5 μm and 10 μm in aerodynamic diameter [PM ], and PM ⩽10 μm in aerodynamic diameter [PM ]), nitrogen dioxide (NO ), and nitrogen oxides (NO ) were estimated by using land-use regression models, and the association between air pollutants and incident lung cancer was investigated by using a Cox proportional hazard model. Furthermore, we constructed a polygenic risk score and evaluated whether air pollutants modified the effect of genetic susceptibility on the development of lung cancer. The results showed significant associations between the risk of lung cancer and PM (hazard ratio [HR], 1.63; 95% confidence interval [CI], 1.33-2.01; per 5 μg/m ), PM (HR, 1.53; 95% CI, 1.20-1.96; per 10 μg/m ), NO (HR, 1.10; 95% CI, 1.05-1.15; per 10 μg/m ), and NO (HR, 1.13; 95% CI, 1.07-1.18; per 20 μg/m ). There were additive interactions between air pollutants and the genetic risk. Compared with participants with low genetic risk and low air pollution exposure, those with high air pollution exposure and high genetic risk had the highest risk of lung cancer (PM : HR, 1.71; 95% CI, 1.45-2.02; PM : HR, 1.77; 95% CI, 1.50-2.10; NO : HR, 1.77; 95% CI, 1.42-2.22; NO : HR, 1.67; 95% CI, 1.43-1.95). Long-term exposure to air pollution may increase the risk of lung cancer, especially in those with high genetic risk.